Allopurinol prevents cardiac and skeletal muscle damage in professional soccer players - Sanchis-Gomar, F.; Pareja-Galeano, H.; Gomez-Cabrera, M. C.; Candel, J.; Lippi, G.; Salvagno, G. L.; Mann, G. E.; Viña, J. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Xanthine oxidase (XO), a free radical-generating enzyme, is involved in tissue damage produced during exhaustive exercise. Our aim was to test whether allopurinol, a powerful inhibitor of XO, may be effective in preventing exercise-induced tissue damage in soccer players. Twelve soccer players were randomized into two experimental groups. One received allopurinol, before a match of the premier Spanish Football League, and the other placebo. Allopurinol prevented the exercise-induced increase in all the markers of skeletal muscle damage analyzed: creatine kinase, lactate dehydrogenase, aspartate aminotransferase, and myoglobin. Creatine kinase-MB isoenzyme and highly sensitive troponin T, specific biomarkers of myocardial injury, increased significantly in the placebo but not in the allopurinol-treated group after the football match. We also found that the exercise-induced lipid peroxidation, as reflected by malondialdehyde measurements, was prevented after allopurinol administration. However, inhibition of XO did not prevent the increment in the activity of alanine aminotransferase found after the match. No changes in the serum gamma glutamyltransferase activity was found after the match on either the placebo and the allopurinol groups. These two enzymes were determined as biomarkers of liver injury. Allopurinol represents an effective and inexpensive pharmacological agent to prevent tissue damage in soccer players.